Faktor-Faktor yang Mempengaruhi Keputusan Pembelian Buah dan Sayur terhadap Penggunaan Aplikasi di Jabodetabek - Hening Restuningtyaswidi; Liska Simamora (Hasanuddin University, 2021)
The research was aimed: (1) To know the characteristics of respondents who use online shop applications to buy fruits and vegetables. (2) To find out which online shopping applications are most used by respondents to buy fruits and vegetables. (3) To know the factors that influence fruits and vegetable purchasing decisions on the use of online shopping applications. Buying decision is the process of the consumer going to buy a product through stages. The rise of buying in Indonesian makes the people enthusiastic to buy fruits and vegetables through online shopping applications. In the Jabodetabek area, shopping trends in the application are higher compared to other areas, especially to shop for fruits and vegetables. This can be seen from the location of the headquarters of several online shopping application platforms located in the Jabodetabek area. Phenomena that occur in the Jabodetabek areas, many people spend their time working from morning to evening, so that they don’t have the time to go to market. The number of samples is 70 respondents. Type of research uses a quantitative descriptive approach. Data obtained from distributing questionnaires. The tool used to analyze is IBM SPSS Statistic 23. The data analysis technique uses validity test, reliability test, classical assumption test, and to determine whether there is an influence of the independent variable on the dependent variable using multiple linear regression. The result of research shows that product quality, service quality, promotion and motivation have a significant effect on purchasing decisions, while price has no effect on purchasing decisions.